Forsythia suspensa extract protects broilers against breast muscle oxidative injury induced by corticosterone mimicked pre-slaughter acute stress. (5th March 2018) - Pan, L; Zhao, P F; Ma, X K; Shang, Q H; Long, S F; Wu, Y; Wang, W; Piao, X S
ABSTRACT: Broilers were used to determine the protective effects of Forsythia suspensa extract (FSE) against breast muscle oxidative injury induced by corticosterone (CS) mimicking pre-slaughter acute stress. A total of 144 male Arbor Acre broilers was randomly allotted to one of 4 treatments in a 2 × 2 factorial arrangement that included FSE supplementation (0 or 100 mg/kg) and subcutaneous injection of CS (0 or 4 mg/kg) at 3 h before slaughter. Corticosterone increased live BW loss, and the adverse effect was attenuated by FSE in broilers subjected to CS ( P < 0.05). Serum levels of CS, uric acid, and glucose were increased, and postmortem breast muscle pH values at 45 min and 24 h were decreased for CS-challenged broilers ( P < 0.05). Corticosterone increased lightness and yellowness values and decreased redness of breast muscle ( P < 0.05), and FSE decreased yellowness and increased redness of breast muscle ( P < 0.05). Drip loss was increased by CS for birds supplemented without FSE ( P < 0.05) and decreased by FSE for birds under CS challenge ( P < 0.05). Corticosterone increased monounsaturated fatty acid (FA) and decreased polyunsaturated FA in breast muscle ( P < 0.05), and saturated FA was decreased and polyunsaturated FA was increased by FSE ( P < 0.05). Malondialdehyde and carbonyl contents in breast muscle were increased by CS and decreased by FSE ( P < 0.05). Inhibition of 1, 1-diphenyl-2-picryl-hydrazyl was decreased by CS and increased by FSE ( P < 0.05). The activities of total-antioxidant capacity, glutathione peroxidase, and superoxide dismutase in breast muscle were lower in birds subjected to CS ( P < 0.05) and were greater in birds supplemented with FSE ( P < 0.05). Collectively, live BW loss and breast muscle oxidative injury were increased by CS in broilers, and these stress-related adverse effects could be attenuated by FSE supplementation via enhanced scavenging ability of free radicals and antioxidant capacity. Therefore, FSE could protect broilers against breast muscle oxidative injury when acute stress happens.